The Swedish University of Agricultural Sciences (SLU) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The Swedish University of Agricultural Sciences (SLU)The Swedish University of Agricultural Sciences is the only agricultural university in Sweden and is the national agricultural research institute responsible to the Ministry of Agriculture. The...